2014
DOI: 10.1007/s00726-014-1775-2
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids and autophagy: cross-talk and co-operation to control cellular homeostasis

Abstract: Maintenance of amino acid homeostasis is important for healthy cellular function, metabolism and growth. Intracellular amino acid concentrations are dynamic; the high demand for protein synthesis must be met with constant dietary intake, followed by cellular influx, utilization and recycling of nutrients. Autophagy is a catabolic process via which superfluous or damaged proteins and organelles are delivered to the lysosome and degraded to release free amino acids into the cytoplasm. Furthermore, autophagy is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
69
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 186 publications
(233 reference statements)
4
69
1
Order By: Relevance
“…Another mechanism by which BCAA may function is by inhibiting the amino acid deficiency sensor, GCN2 and reversing eIF2α phosphorylation[132], impaired protein synthesis and improve muscle mass. Finally, leucine directly activates mTORC1 that stimulates protein synthesis and decreases autophagy[133], both of which have the potential to improve muscle mass. A recent study in human cirrhosis reported that a leucine enriched BCAA mixture was able to reverse the molecular perturbations in the skeletal muscle downstream of myostatin in cirrhotic patients[66].…”
Section: Management Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another mechanism by which BCAA may function is by inhibiting the amino acid deficiency sensor, GCN2 and reversing eIF2α phosphorylation[132], impaired protein synthesis and improve muscle mass. Finally, leucine directly activates mTORC1 that stimulates protein synthesis and decreases autophagy[133], both of which have the potential to improve muscle mass. A recent study in human cirrhosis reported that a leucine enriched BCAA mixture was able to reverse the molecular perturbations in the skeletal muscle downstream of myostatin in cirrhotic patients[66].…”
Section: Management Strategiesmentioning
confidence: 99%
“…Myostatin antagonists[91], direct mTORC1 activators[66, 133], antioxidants, and mitochondrial protective agents have the potential to benefit skeletal muscle protein turnover but have not been adequately evaluated. Careful mechanistic studies are necessary with preclinical testing before these interventions can be translated to clinical practice.…”
Section: Management Strategiesmentioning
confidence: 99%
“…For example, chronic (6 mo) ED increases mRNA and protein markers of autophagy (53). Autophagy degrades, via lysosomal proteolysis, protein aggregates and damaged organelles that are then "recycled" to yield energy to maintain cellular metabolism (11). This process commences with the sequestration of a portion of cytoplasm by a double-membrane vacuole called the autophagosome, which subsequently releases its contents for degradation upon fusion with the lysosome (37).…”
mentioning
confidence: 99%
“…Another major nutrient-sensing pathway is the mammalian target of rapamycin (mTOR) signaling pathway, which senses and integrates diverse environmental perturbations such as changes in the nutritional state and infections (281,282). mTOR affects cellular physiology by controlling many fundamental cellular processes, such as cell division, autophagy, cellular growth, and senescence, and it is involved in several pathological states such as obesity, type 2 diabetes, and cancer (281,282).…”
Section: Control Of DC Activation By Mtormentioning
confidence: 99%
“…mTOR affects cellular physiology by controlling many fundamental cellular processes, such as cell division, autophagy, cellular growth, and senescence, and it is involved in several pathological states such as obesity, type 2 diabetes, and cancer (281,282). mTOR interacts with several proteins to form two large protein complexes, mTORC1 and mTORC2, both of which contain the catalytic mTOR subunit (281,282). The rapamycinsensitive mTORC1 pathway, which contains the adaptor protein Raptor, can sense diverse stimuli such as growth factors, stress, energy status, oxygen, and amino acids to control many processes, including protein and lipid synthesis and autophagy.…”
Section: Control Of DC Activation By Mtormentioning
confidence: 99%